Calculating noise levels
Explore these skills in a real world context.
What is a logarithm? The logarithm of a number is the power that the base must be raised to, to give that number. The logarithm of 16 with a base of 2 is 4, because 2to the power of 4 = 16.
The modeling of growth and decay in areas such as finance, epidemiology and science makes use of equations with logarithms and exponentials. For example the equation \(\log_{e}\frac{N}{N_{0}}\approx-\lambda t\) is used to describe radioactive decay. The laws for working with logarithms enable us to solve equations that cannot be solved with other algebraic techniques.
The logarithm of a number is the power to which the base must be raised to produce the number. This means that a logarithm (or log) is an index. Every index or log expression contains a number, a base and an index. For example:
And we say " eight is equal to two to the power of three".
This statement has an equivalent logarithmic form and may be written as:
We say “the log to base two of eight is equal to three” (the power of two that gives eight is three).
Generally, providing \(a>0,\ n>0\) and \(a\neq1\),
\[ a^{x}=n\Leftrightarrow\log_{a}n=x \]
While any positive number except one can be the base of a logarithm, \(10\) and \(e\) are most common.
To find the power of \(10\) that produces \(50\) we use the LOG button on the calculator: \(\log_{10}50\approx1.7\) and \(10^{1.7}\approx50\).
To find the power of \(e\) that produces \(50\) we use the LN button on the calculator: \(\log_{e}50=\ln50\approx3.9\) and \(e^{3.9}\approx50\).
To evaluate a logarithm it may be helpful to create an equation and change to index form.
Corresponding to the three index laws, there are three laws of logarithms to help in manipulating logarithms. If \(m,n>0\) and \(a>0,\ a\neq1\) then
The laws can be used to simplify and evaluate logarithmic expressions
The laws of logarithms can be used to solve equations involving logarithms or in which the variable is a power.
\[\begin{align*} 2^{x-3} & =10\\ \log_{10}2^{x-3} & =\log_{10}10\ \textrm{(take logs of both sides)}\\ (x-3)\log_{10}2 & =\log_{10}10\\ (x-3)(0.301) & =1\ (\textrm{use a calculator to find}\log_{10}2)\\ x-3 & =\frac{1}{0.301}\\ x & =3+\frac{1}{0.301}\\ x & =6.32 \end{align*}\]
Write in logarithm form
a) \(3^{2}=9\)
b) \(10^{4}=10000\)
c) \(10^{-2}=0.01\)
d) \(e^{a}=b\)
\[\begin{array}{llll} a)\,\log_{3}9=2 & b)\,\log_{10}10000=4 & c)\,\log_{10}0.01=-2 & d)\,\log_{e}b=a.\end{array}\]
Evaluate without using a calculator
a) \(\log_{7}49\)
b) \(\log_{10}\sqrt{10}\)
c) \(\log_{5}1\)
d) \(\log_{10}100000\)
e) \(\log_{5}5\)
\[\begin{array}{lllll} a)\,2 & b)\,1/2 & c)\,0 & d)\,5 & e)\,1\end{array}\]
Simplify
a) \(\log_{4}8+\) \(\log_{4}3\) \(-\log_{4}2\)
b) \(\frac{1}{2}\log_{10}25-\) \(\log_{10}4\)+2\(\log_{10}3\)
c) \(\log_{e}e^{2}+2\) \(\log_{e}3-\) \(\log_{e}18\)
d) \(\log_{a}4+2\) \(\log_{a}3\)–\(2\log_{a}6\)
e) \(\frac{1}{2}\log_{10}a^{2}+3\) \(\log_{10}b-\) \(\log_{10}3ab^{2}\)
\[\begin{array}{lllll} a)\,\log_{4}12 & b)\,\log_{10}\left(45/4\right) & c)\,2-\log_{e}2 & d)\,0 & e)\,\log_{10}b-\log_{10}3\end{array}\]
Solve for \(x\)
a) \(\log_{10}x=\log_{10}4-\log_{10}2\)
b) \(\log_{2}2x-\) \(2\log_{2}3\) \(=\) \(\log_{2}6\)
c) \(10^{m+1}=7\)
\[\begin{array}{lll} a)\,x=2 & b)\,x=27 & c)\,m=-0.155\end{array}\]
Unless otherwise labeled, images on this page by RMIT, licensed under CC BY-NC 4.0